Central Maintenance Spin-Off Creation towards Digitalization Focused on the Parent Company: A Case Study of Integrated Steel Corporation (ISC) in Indonesia - Imaduddin, Dani Akhmad; Wandebori, Harimukti; Hamsal, Mohammad (Bina Nusantara University, 2024)
The steel industry plays a crucial role in national development. Major global steel producers such as the United States, Russia, and Japan have seen declines due to the rise of China as a dominant steel producer. Integrated Steel Corporation (ISC) in Indonesia has also faced declining performance, with its market capitalization dropping by 68.9% over the past eight years. The research primarily aimed to analyze customer preferences in the maintenance industry and determine positioning strategies. Additionally, it sought to identify the factors driving the formation of the Strategic Maintenance Services (SMS) spin-off from ISC and propose strategies for SMS to achieve a competitive advantage. Data were collected qualitatively through interviews and Focus Group Discussions (FGDs) with customers to understand their perspectives, SMS management to grasp core business competencies and strategy, and ISC management to understand the parenting strategy. The results show several internal dynamics within ISC drove the formation of the SMS spin-off: 1) the transformation of the parent company; 2) short circuit incident at the main ISC factory; and 3) the cost burden of maintenance support. External factors indicate rapid industrial growth and the company's strengthening as a group after experiencing losses for almost a decade. The proposed strategy for SMS involves leveraging ISC’s subsidiaries and joint venture companies for centralized service maintenance. SMS aims to offer customized one-stop maintenance solutions with high quality at competitive prices by enabling Digital Maintenance Information (DMI). The target markets include large industries in steel manufacturing, petrochemicals, flour mills, cement, and logistics.